2017
DOI: 10.18632/oncotarget.15402
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal binding protein-2 promotes cell proliferation and migration in breast cancer via suppression of p16INK4A

Abstract: C-terminal binding protein-2 (CtBP2) enhances cancer proliferation and metastasis. The role and mechanism of CtBP2 in breast cancer remains to be elucidated. Western blot and immunochemistry were employed to evaluate the level of CtBP2 and p16INK4A in breast cancer. Genetic manipulation was used to study the expression of p16INK4A and its downstream genes regulated by CtBP2. Functional assays, including colony formation, wound healing, transwell invasion, anchorage-independent growth assay and a xenograft tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Prostate cancer is the most common malignant tumour in men of developed countries and the second leading cause for death among male cancer patients. GGNBP2 is located in the human chromosome 17q12‐21.1 region, and the genes encoded in this region are closely related to the progression of breast cancer (Yang et al, ), ovarian cancer (May et al, ), laryngeal cancer (Chen et al, ) and glioma (Zhan et al, ). In tumour cells, the normal processes of gene transcription and cleavage are disrupted, and abnormal mutations in genes and disorders in transcription and translation processes can lead to the synthesis of mRNA that does not exist originally, or the proportion of transcription or translation of different cuts.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is the most common malignant tumour in men of developed countries and the second leading cause for death among male cancer patients. GGNBP2 is located in the human chromosome 17q12‐21.1 region, and the genes encoded in this region are closely related to the progression of breast cancer (Yang et al, ), ovarian cancer (May et al, ), laryngeal cancer (Chen et al, ) and glioma (Zhan et al, ). In tumour cells, the normal processes of gene transcription and cleavage are disrupted, and abnormal mutations in genes and disorders in transcription and translation processes can lead to the synthesis of mRNA that does not exist originally, or the proportion of transcription or translation of different cuts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CtBP2 has a critical function in tumorigenesis and tumor progression (20,21). CtBP2 is overexpressed in a number of different tumor types, including hepatocellular carcinoma (22), prostate cancer (23), breast cancer (24,25) and ovarian cancer (26). Furthermore, preliminary studies conducted by the present research team revealed that the…”
Section: Introductionmentioning
confidence: 61%
“…1B). CTBPs are co-repressors which are implicated in human cancer by promoting several pro-oncogenic activities including EMT, cell survival, migration and invasion (28)(29)(30). We validated the interactions by co-immunoprecipitation in multiple experiments using different antibodies directed to ZBTB18 or CTBP2 (Fig.…”
Section: Zbtb18 Interacts With Ctbp2 Through the Vldls Motifmentioning
confidence: 97%